Unexpected reproductive fidelity in a polygynous frog - de Sá, Fábio P. [UNESP] (2020)
Polygynous mating systems with group fidelity are a common animal organization, typically consisting of multiple females in a mated group with a single male for an extended period (sometimes referred to as harem polygyny). Single-male polygyny with reproductive fidelity occurs in invertebrates, bony fishes, and some tetrapods, such as lizards, mammals, and birds. In amphibians, reproductive fidelity in polygynous groups is not fully demonstrated. Combining data on larval development, molecular paternity assignment, and in situ behavioral observations, we reveal high fidelity during a prolonged breeding season in a Neotropical polygynous frog. Males dominate scarce breeding sites, guarding offspring, and mating exclusively with multiple females that exhibit dominance rank. This system likely evolved in response to intense competition for breeding sites and intrasexual competition for mates.